Fabrication of zein nanofibrous scaffold containing Scrophularia striata extract for biomedical application - Yasin Salahshour; Saadat Rastegarzadeh; Hossein Motamedi; Elham Hoveizi (Journal of Biological Engineering)
Abstract Skin wounds have the potential to rapidly become infected, with bacteria having the ability to quickly penetrate to the skin’s deeper layers. Then they enter the lymph nodes and spread throughout the body; therefore, all wounds should be cleaned and have a permanent cover. Modern wound dressings with effective antibacterial and therapeutic properties are required to create a sterile environment for the acceleration of healing. The aim of this work was to prepare zein electrospun nanofibers containing Scrophularia striata extract for wound healing promotion. Electrospun nanofibers made of zein, a natural polymer, have attracted a lot of attention due to their biocompatibility and biodegradability. The prepared nanofibers were characterized by scanning electron microscopy (SEM), energy dispersive X‑ray analysis (EDX), water contact angle test, and Fourier transform infrared spectroscopy (FT-IR). The parameters affected by the electrospinning process were investigated and optimized. The results revealed that the zein nanofibers (25% w/v, zein) containing Scrophularia striata extract (6.7% w/v) had a smooth and bead-free morphology with improved surface hydrophilicity. The measurement of water contact angle confirmed that nanofibers containing extract showed higher wettability (64.9°) compared to fibers without extract (119.8), so the proposed mat adequately moisturizes the wound environment. The antimicrobial studies show that Scrophularia striata extract incorporated nanofibers has the ability to inhibit the growth of both gram-negative and gram-positive bacteria. The biophenols release profile indicated that nanofibrous mat can release more effective substances to promote wound healing. The biocompatibility and biodegradability of nanofibrous scaffold containing Scrophularia striata extract tested in in vivo and in vitro conditions show a significantly higher survival rate of fibroblast cells. In addition, macroscopic and histological observations confirmed that the implanted nanofibers containing the extract did not exhibit any signs of inflammation or redness after a month when inserted beneath the skin of mice surrounded by vessels containing epidermis. Graphical Abstract